Repercussion of the death of Fidel Castro in Santiago de Cuba. Appearance and evolution of the event in the political and media agendas - Muñiz Zúñiga, Viviana (Estudios sobre el Mensaje Periodístico, 2018)
The death of Fidel Castro on November 25, 2016 impacted Cuban society, mainly the media responsible for providing information coverage to the event. This research explains the relationship between the political and media agendas during the event in the province of Santiago de Cuba, where the ashes of the revolutionary leader now rest. Techniques such as content analysis, Spearman correlation, interviews and discussion groups with journalists were used to characterize the information coverage of the topic from the experiences of the professionals who participated in it. The study explains the evolution phases of this event in the agendas analyzed: that of the irruption of the theme, permanence in the agenda and decay and possible appearance of a new object, which is visualized through a diagram that allows to understand the process in Each step.